Cyberbullying: An Analysis of the impact aof crime phenomena in the digital era on the social life of society - Hamid*, Supardi; Saka, Octalya; Rusmawan, Teddy (Riwayat: Educational Journal of History and Humanities, 2023)
The phenomenon of cyberbullying has become a serious issue that has emerged in conjunction with the development of digital technology in the modern era. This article analyzes the impact of this criminal phenomenon on the social life of the community in the context of the digital era. In this analysis, we highlight the behavioral changes and social dynamics caused by the spread of cyberbullying, as well as its implications for well-being and social interaction. The research method used in this study is qualitative research. The research results indicate that the rapid growth of digital technology has brought complex consequences to human social life. One prominent impact is the emergence of the phenomenon of cyberbullying. This analysis demonstrates how such behavior has altered the way communities interact, communicate, and experience psychosocial effects. Cyberbullying has significantly impacted the social life of the community. A society that was previously connected by technology is now facing the risk of division due to derogatory treatment through digital media. This has an impact on the quality of social interactions, where feelings of safety and trust in interaction can be eroded by uncertainty about potential negative treatment.